Estratégias de generalização de padrões de alunos do ensino fundamental do ponto de vista de seus professores - Almeida, Maria Margarida Massignan de (2006)
The purpose of this study is check if the middle school (11 to 15 years old students) teachers from public schools of a small town in the state of SP work with activities that involve the observation of regularity and patterns generalization. If they do, the aim is to know which strategies of resolutions the teachers foresee their students will use. It was carried out a semi-structured interview with five teachers from the state chain to collect data. All the analysed data have shown that teachers work with such activities sporadically in the classroom. They do foresee the priority of counting and drawing strategies, although they suggest that they would work with resolution strategies which include a generalization without a more rigorous algebric formation